1990
DOI: 10.1111/j.1752-0606.1990.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Supervision in Family Therapy: A Decade Restudy*1

Abstract: This paper reports on a 10‐year replication of Everett's (1980) survey of Approved Supervisors of the American Association for Marriage and Family Therapy (AAMFT). Significant differences were found between today's supervisors and supervision, including an increase in female supervisors, a shift toward a systemic theoretical orientation, greater concentration of supervisors in formal training settings, a great increase in the use of video recordings, a decline in the popularity of personal psychotherapy as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…For instance, in a human service clinical employment setting, family therapy clinicians may not be able to choose their clinical supervisor because of work assignments. Nichols et al (1990) found that 70.8% of family therapy supervision occurred as part of employment.…”
Section: Supervision: Definition and Descriptionmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, in a human service clinical employment setting, family therapy clinicians may not be able to choose their clinical supervisor because of work assignments. Nichols et al (1990) found that 70.8% of family therapy supervision occurred as part of employment.…”
Section: Supervision: Definition and Descriptionmentioning
confidence: 97%
“…Family therapy clinicians have been encouraged to pursue supervision as a quality control measure and professional growth development aid to serve as a professional clinical vehicle for change. Nichols et al (1990) demonstrated that 90% of COAMFTE approved supervisors rated the need for clinician supervision as ''important'', ''very important'', or even higher.…”
Section: Supervision: Definition and Descriptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rather, family therapy training procedures (with live supervision being the main mode of training), is similar to that of training supervisors-to-be: The apprenticeship model is complemented with advanced theoretical courses in family therapy (Nichols, Nichols & Hardy, 1990). The need for formal training of family therapists became apparent with the growing number of training programs (Keller, Protinsky, Lichtman, & Allen, 1996;Liddle, Breunlin & Schwartz, 1988;Constantine, Piercy & Sprenkle, 1986;Liddle et al, 1984).…”
Section: Introductionmentioning
confidence: 97%
“…designation (Everett, 1980;Lee, Nichols, Nichols, & Odom, 2004;Nichols, Nichols, & Hardy, 1990) have been important sources of information on the changes. Among the more striking developments has been the increase in Approved Supervisors holding a master's degree as their highest clinical degree.…”
mentioning
confidence: 99%